Ethical leadership as a predictor of teachers’ task performance in public secondary schools in Delta State, Nigeria - Ifunanya Nkechi Ohamobi; Mark Okem Maha (PT. Pena Produktif Kreatif, 2026)
This study examined ethical leadership as a predictor of teachers’ task performance in public secondary schools in Delta State, Nigeria. Four research questions and four null hypotheses guided the study. A correlational research design was adopted. population comprised 11,011 teachers in public secondary schools across the 25 Local Government Areas of Delta State. A sample of 551 teachers was selected using proportionate stratified and simple random sampling techniques. Data were collected using two researcher-developed instruments: the Ethical Leadership Questionnaire (ELQ) and Teachers’ Task Performance Questionnaire (TTPQ). The instruments were validated by experts in Educational Management and Measurement and Evaluation, while reliability was established using Cronbach Alpha, which yielded an overall coefficient of 0.750. Data were analysed using simple regression analysis at the 0.05 level of significance with the aid of SPSS version 27. The findings revealed that ethical leadership significantly predicted teachers’ task performance. Specifically, dimensions such as integrity, fairness, accountability, effective communication, participatory decision-making, and professional conduct positively influenced teachers’ effectiveness in carrying out instructional and school-related responsibilities. The study concluded that ethical leadership is essential for improving teachers’ task performance in public secondary schools. It was therefore recommended that principals should uphold ethical standards, encourage participatory leadership practices, and maintain transparent communication to enhance teachers’ effectiveness and overall school productivity.